2006
DOI: 10.1196/annals.1383.006
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile of Abdominal Aortic Aneurysm Rupture

Abstract: To search for novel transcriptional pathways that are activated in abdominal aortic aneurysm rupture, cDNA microarrays were used to compare global mRNA expression at the aneurysm rupture edge to anterior sac, and selected results were confirmed using quantitative real-time-polymerase chain reaction (QRT-PCR). This study identified apoptosis, angiogenesis, and inflammation as potentially important participants during the process of aneurysm rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…In a similar manner, longitudinal experiments by Choke et al (2006, 2009) investigated genes involved in aneurysm rupture by comparing mRNA expression within biopsies collected at the site of rupture with control biopsies sourced from the same patient. Pilot data confirmed that increased expression of genes involved in apoptosis, angiogenesis and inflammation may contribute towards AAA rupture 181. These findings were expanded in a stringent follow-up study, identifying 139 significant changes in gene expression between ruptured, and non-ruptured AAA biopsies (>2.5 fold increase/decrease in expression, P<0.005).…”
Section: 0 Future Prospects Of Aaa Diagnosis and Monitoringmentioning
confidence: 65%
“…In a similar manner, longitudinal experiments by Choke et al (2006, 2009) investigated genes involved in aneurysm rupture by comparing mRNA expression within biopsies collected at the site of rupture with control biopsies sourced from the same patient. Pilot data confirmed that increased expression of genes involved in apoptosis, angiogenesis and inflammation may contribute towards AAA rupture 181. These findings were expanded in a stringent follow-up study, identifying 139 significant changes in gene expression between ruptured, and non-ruptured AAA biopsies (>2.5 fold increase/decrease in expression, P<0.005).…”
Section: 0 Future Prospects Of Aaa Diagnosis and Monitoringmentioning
confidence: 65%
“…Choke et al 19 in 2006 identified activation of apoptosis, angiogenesis, and inflammation transcriptional pathways in AAA rupture regions. These results are not in accordance with our results, ie, high rupture risk region samples did not show more congruent gene expression patterns than low rupture regions.…”
Section: Discussionmentioning
confidence: 99%
“…These constantly evolving technologies may lead to the discovery of new biomarkers for AAA rupture risk. Among hundreds of genes that were found to be differentially expressed in the rupture edge as compared to the anterior sac of AAA tissues, many of them encode factors that are involved in angiogenesis, inflammation and apoptosis [136]. Some of these features/pathways have been extensively studied in other diseases such as atherosclerosis and cancer [137141].…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%